Spatial scale-dependence of ecosystem CO2 exchange in three nonarborescent temperate vegetations - Czóbel, Szilárd (Acta Biologica Szegediensis, 2002)
Our goal was to investigate the spatial scale-dependence of synphysiological measurements in three different vegetation types: a loess stepp e grassland, a sandy grassland and a ruderal weed community. The former two are widely distributed in the Carpathian Basin and completed with the weed association these are well representing the Hungarian non-arborescent, herbaceous vegetation. To carry out the stand physiological measurements we have constucted gas exchange chambers of several sizes. This size series allowed us to investigate the scale dependence of gas exchange measurements. In all of the three investigated vegetation the variability of C02 -assimilation showed spatial scale-dependence. The highest variability was seen at smaller scales (smaller chamber sizes). The variability of the spatial scale-dependence of the stand photosynthesis was the highest in the sandy grassland, the least organised out of the three investigated community.